Un algoritmo basado en búsqueda tabú granular para la solución de un problema de ruteo de vehículos considerando flota heterogénea (2014)
This paper considers the vehicle routing problem with heterogeneous fleet (VRPH), which tries to determine the routes to be constructed for satisfying the demand of the customers by considering a fleet of vehicles with different capacities and costs not homogeneous. The main objective is to minimize the distance traversed by the different vehicles. This paper proposes a metaheuristic algorithm based on a granular tabu search for the solution of the problem. The algorithm allows infeasible solutions by penalizing them by a dynamic factor which is adjusted during the search. Computational experiments on real instances for a Colombian company show that the proposed algorithm is able to obtain, within short computing times, better solutions for those obtained by the current traditional method for planning the routes.